2020
DOI: 10.1111/aos.14696
|View full text |Cite
|
Sign up to set email alerts
|

Retinal vessel diameters, flicker‐induced retinal vasodilation and retinal oxygen saturation in high‐ and low‐risk pregnancy

Abstract: Purpose To compare retinal vascular parameters between high‐risk and low‐risk pregnant women over time during pregnancy. Methods In a longitudinal study, we included pregnant women with normal blood pressure and normal body mass index (BMI, group 1), pregnant women with systemic hypertension and/or overweight (group 2) and age‐matched nonpregnant healthy women (group 3). Using the dynamic vessel analyser (DVA) we investigated flicker‐induced vasodilation in retinal arteries (FLA) and veins (FLV), central retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…However, it must be noted that these risk factors may simply work primarily at the level of the occlusion rather than secondarily with hypoxic outcomes. Interestingly, pregnancy has also been associated with alterations in retinal vessel diameters and oxygen saturation (Sharifizad et al 2021). Chronic kidney disease, optic neuritis associated with multiple sclerosis, and coronary artery bypass surgery have all recently been associated with alterations in retinal oxygenation saturation as well (Dinesen et al 2020; Svrcinova et al 2020; Liu et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…However, it must be noted that these risk factors may simply work primarily at the level of the occlusion rather than secondarily with hypoxic outcomes. Interestingly, pregnancy has also been associated with alterations in retinal vessel diameters and oxygen saturation (Sharifizad et al 2021). Chronic kidney disease, optic neuritis associated with multiple sclerosis, and coronary artery bypass surgery have all recently been associated with alterations in retinal oxygenation saturation as well (Dinesen et al 2020; Svrcinova et al 2020; Liu et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the arteriolar and venular saturation indices, similar median values were found in the HDP and control groups. One other study investigated RO in women with either hypertension (both pre‐existing and gestational) or overweight grouped together ( n = 25, 17 of whom with hypertension) during pregnancy and 1–5 days postpartum (Sharifizad et al., 2021). The authors found no alterations in the SaO 2 compared to controls.…”
Section: Discussionmentioning
confidence: 99%